Online learning during the Covid-19 pandemic: the experiences and perceptions of undergraduate occupational therapy students at two Australian universities - Brown Ted; Robinson Luke; Gledhill Kate; Peart Annette; Yu Mong-Lin; Isbel Stephen; Greber Craig; Etherington Jamie (Sciendo, 2021)
To investigate if first-year occupational therapy students who have had no on-campus, face-to-face learning experiences differed from second-, third- and fourth-year students in their perceptions and experiences of online learning during the Covid-19 pandemic.